Evolution of Durability and Mechanical Behaviour of Mud Mortar Stabilized with Oil Shale Ash, Lime, and Cement - Walid Fouad Edris; Hamza Al-Fhaid; Mahmoud Al-Tamimi (Salehan Institute of Higher Education, 2023)
The investigation into earthen construction technologies and materials is now acknowledged as a crucial area requiring further research. Earthen mortars are prevalent in both modern and traditional construction due to the abundance of earth material, their favorable thermal properties, and their low embodied energy. The objective of this study is to support the use of natural materials collected from north Jordan to enhance the mechanical properties and durability of mud mortar. The local soil was stabilized using Oil Shale Ash (OSA), Ordinary Portland Cement (OPC), and lime for producing mud mortar. Particle size analysis, plastic limit, liquid limit, XRD, and XRF were applied to assess the geotechnical characterization and mineral composition of the earthen stabilizers and local soil. In order to examine the mechanical properties (specifically compressive strength) and durability characteristics (such as water absorption and shrinkage) of mud mortar, a total of 8 mixtures were prepared. One of these mixtures served as a control, while the others were created by substituting soil with varying proportions of OSA, cement, and lime. The results show that the mud mortar contained 10% OSA and 10% cement, which exhibited the highest compressive strength. Moreover, an increase in the proportion of OSA in the soil led to a decrease in absorption and linear shrinkage, indicating that OSA is an effective stabilizing agent for mud mortar.Â Doi: 10.28991/CEJ-2023-09-09-06 Full Text: PDF